2019
DOI: 10.1186/s12936-019-2873-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of anti-malarial acylphenoxazine derivatives prepared from basic blue 3

Abstract: Background Basic blue 3 is a promising anti-malarial lead compound based on the π-delocalized lipophilic cation hypothesis. Its derivatives with nitrogen atoms bonded to carbon atoms at the 3- and 7-positions on the phenoxazine ring were previously shown to exert potent antiprotozoal activity against Plasmodium falciparum , Trypanosoma cruzi , Trypanosoma brucei rhodesiense , and Leishmania donovani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A follow‐up study showed that this compound inhibited growth of all stages, but affected ring‐stage parasites in particular at low concentration [40] . More recently, a series of acylphenoxazine compounds with low cytotoxicity against HEK293T and HepG2 cells, but potent selectivity for Plasmodium strains has been reported [41] . While the literature certainly points to the antimalarial potential of phenoxazine derivatives, this scaffold has not been considered specifically with respect to HZ inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A follow‐up study showed that this compound inhibited growth of all stages, but affected ring‐stage parasites in particular at low concentration [40] . More recently, a series of acylphenoxazine compounds with low cytotoxicity against HEK293T and HepG2 cells, but potent selectivity for Plasmodium strains has been reported [41] . While the literature certainly points to the antimalarial potential of phenoxazine derivatives, this scaffold has not been considered specifically with respect to HZ inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…[40] More recently, a series of acylphenoxazine compounds with low cytotoxicity against HEK293T and HepG2 cells, but potent selectivity for Plasmodium strains has been reported. [41] While the literature certainly points to the antimalarial potential of phenoxazine derivatives, this scaffold has not been considered specifically with respect to HZ inhibition. Thus given its highest overall ranking (3 rd place) for a nonantimalarial scaffold with respect to adsorption to the crystal surface, phenoxazine (T9) was our scaffold of choice moving forward to experimentally validate the adsorption hypothesis.…”
Section: Adsorption Of Cyclic Scaffolds Onto the Crystal Facesmentioning
confidence: 99%
“…The absorbance was measured using a microplate reader at 570 nm and 630 nm wavelengths. The percentage growth inhibition was calculated after subtracting the background and the blank followed by the determination of the IC 50 value from the dose–response curve (Davis et al, 2012; Riss et al, 2016; Tougan et al, 2019). The selectivity index is a measure of relative effectiveness and safety of an investigational drug which can be determined as the ratio of the cytotoxic concentration to the effective bioactive concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Since Guttmann and Ehrlich reported the clinical cure of two patients after oral administration of a synthetic dye, methylene blue which contains a phenothiazine moiety, in 1891, numerous synthetic dyes were investigated for their antimalarial properties [ 16 , 80 ]. The only adverse effect they reported was ‘periodic irritation of the bladder’ which was somewhat alleviated by taking nutmeg powder.…”
Section: Phenoxazine As Antimalarial Drugmentioning
confidence: 99%